Pemberdayaan Struktur dan Agen dalam Penanggulangan Kemiskinan Kultural di Desa Tianyar Barat Kabupaten Karangasem Bali - A A Ngurah Anom Kumbara; Mayske Rinny Liando; Nanang Sutrisno (Universitas Udayana, 2023)
In the last five years, Karangasem Regency has always occupied the top position in the number of poor people in Bali Province. One of the pockets of poverty in Karangasem Regency is West Tianyar Village, Kubu District. In addition to natural and structural factors, cultural factors are the causes of poverty in the village. The purpose of this study is to uncover the determinants of the formation of cultural poverty and find the method of empowerment of the role of structures and agents in poverty reduction in this region. Data was collected through observation, interview, and document analysis techniques. Data is analyzed by structuration theory (agency-structure) as the basis for interpretation. This study found that poverty always involves the circularity of the relationship between natural, structural, and cultural poverty so that it is difficult for people to overcome the conditions of poverty faced. By empowering the role of structures and agents, efforts to solve the problem of cultural poverty in West Tianyar Village can gradually be eliminated.